2020
DOI: 10.3390/su12187669
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of Fintech: Focused on Uncertainty and Perceived Quality Issues

Abstract: Despite high expectations for the growth of Fintech, it has not reached the expected growth in the real world. As Fintech is innovative but inherently unpredictable, customers are still hesitant to adopt and use Fintech, which ultimately affects its growth. To achieve the sustainable development and growth of Fintech, an in-depth investigation of Fintech continuance intentions is required. To investigate continuous-use behavior in a Fintech context, this study focuses on two relevant issues: uncertainty and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 60 publications
5
73
0
2
Order By: Relevance
“…As two thirds of Brazilians are currently in debt and one fourth have delayed repayments [94], the danger of over-indebtedness and the need to protect consumers from predatory agents are quite pressing issues that cannot be neglected [31,95]. Consequently, government and regulators will have to pursue a balance between the ease of collection and enforcement of guarantees and appropriate consumer protection [96]. It is worth remembering that the difficulty in providing guarantees is one of the main obstacles to financial inclusion in Brazil [68].…”
Section: Discussionmentioning
confidence: 99%
“…As two thirds of Brazilians are currently in debt and one fourth have delayed repayments [94], the danger of over-indebtedness and the need to protect consumers from predatory agents are quite pressing issues that cannot be neglected [31,95]. Consequently, government and regulators will have to pursue a balance between the ease of collection and enforcement of guarantees and appropriate consumer protection [96]. It is worth remembering that the difficulty in providing guarantees is one of the main obstacles to financial inclusion in Brazil [68].…”
Section: Discussionmentioning
confidence: 99%
“…Ease of use also contributes to the loyalty intentions of the customer [78,79]. Ease of use helps reduce the anticipated stress of adopting a fintech service [80,81]. Fintech companies favour ease of use through a multi-stage mechanism of conscientization, capacitation, incentivization, enrichment and cultivation [82].…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…Time is an important asset, especially because fintech services are used both by individuals and companies to gain efficiency and productivity. Customers engage with fintech companies to avoid travel to brick-and-mortar locations, to perform e-services and to beneficiate from the speed and ease of use associated with new technologies [81,85]. Perceived transaction speed influences the perceived effort to engage with fintechs, while the perceived transaction speed positively influences the behavioural intention to continue the relations with fintechs [100].…”
Section: Hypothesis 4 (H4) Assurance Is Positively Associated With Customer Experiencementioning
confidence: 99%
“…Because of the large and high-dimensional data involved in the service, the function of TR in financial technology application scenarios is even more essential. Previous research has shown the factors that affect TR in fintech innovation adoption, such as customer service and satisfaction [24]; brand image, government support, perceived risk [15]; and information quality and service quality [25]. Therefore, it is important to research how TR affects the attitudes of potential users and their willingness to adopt.…”
Section: ) Perceived Usefulnessmentioning
confidence: 99%